2011
DOI: 10.1002/pola.24852
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)‐catalyzed base‐free oxidative homocoupling of fluorene diboronic acid ester: A new approach for the synthesis of π‐conjugated polymers

Abstract: A new route, Pd(II)‐catalyzed base‐free oxidative homocoupling, has been successfully used for the synthesis of polyfluorene. Using only diboronic esters and a stable Pd(II) catalyst in the absence of base can greatly simplify the synthetic condition of conjugated polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Removing the fractions with low molecular weight by precipitation of the obtained polymer in a mixture solvent of THF and methanol (2 : 1, v/v) gave a polymer fraction with a M n of 11 960 and a PDI of 1.34. This result is superior to that previously reported by our group via the Pd(II)-catalyzed oxidative homopolymerization of diboronic esters, 24 suggesting that Fe(III) catalyzed oxidative homocoupling can give a high molecular weight of PFO which can meet the requirements of optoelectronic devices.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Removing the fractions with low molecular weight by precipitation of the obtained polymer in a mixture solvent of THF and methanol (2 : 1, v/v) gave a polymer fraction with a M n of 11 960 and a PDI of 1.34. This result is superior to that previously reported by our group via the Pd(II)-catalyzed oxidative homopolymerization of diboronic esters, 24 suggesting that Fe(III) catalyzed oxidative homocoupling can give a high molecular weight of PFO which can meet the requirements of optoelectronic devices.…”
Section: Resultscontrasting
confidence: 75%
“…23 Previously, we have reported the synthesis of polyfluorene using a Pd(II)-catalyzed base-free oxidative homocoupling reaction of diboronic esters. 24 Our interest is to find cheap and practical methods for the synthesis of p-conjugated polymers. Thus, as part of an extended investigation, in this study we report the synthesis of p-conjugated polymers using the ligand-free iron(III)-catalyzed oxidative homocoupling of Grignard reagents.…”
Section: Introductionmentioning
confidence: 99%
“…These reports showed that a bimetallic approach to homocoupling was possible, allowing for wet benchtop coupling conditions and green solvents, such as ethanol. However, in previous reports the catalyst loading for dimerization was high (5–10% Pd). , More recently, coupling of phenyl hydrazines suggested that catalytic amounts of copper­(II) could be used instead of stoichiometric amounts . However, the yields were generally moderate with a limited substrate scope when performed in water.…”
mentioning
confidence: 98%
“…However, these reactions can call for specialized equipment to maintain an inert atmosphere, high temperatures, and/or specialized catalysts . Previous literature has shown that palladium-catalyzed homocoupling of diboronates is an effective strategy for making small polyfluorenes . However, these synthetic strategies required a pure oxygen atmosphere at 80 °C under strictly dry conditions which could trigger combustion on a reactor scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation